The Influence of Organizational Culture and Behavior of Micro, Small and Medium Enterprises on MSME Performance in Tangerang Regency (Case Study of MSME Actors in Tangerang Regency Using a Mixed-Method Approach) - Sarwani Sarwani; Denok Sunarsi; Moh. Sutoro (Jurnal Manajemen Industri dan Logistik, 2022)
The purpose of this study was to identify the influence of organizational culture and behavior of Micro, Small and Medium Enterprises on MSME performance in South Tangerang. This research method uses a Mixed Method approach by combining quantitative research and qualitative research. The quantitative method uses SEM modeling (Smart PLS 3.0) and the qualitative method through interviews, observations and documentation that discusses the themes of culture, behavior and performance of MSMEs. The results of the quantitative research show that Organizational Culture has no significant effect on MSME performance because the T-Statistic value is 0.519 < 1.984 and P-Values = 0.604 > 0.05 On the other hand, behavioral variables of MSME actors have a significant impact on MSME performance due to the t-statistic value is 2.631. > 1.984 and P-Values = 0.009 < 0.05. As for the results of qualitative research, to improve the performance of MSMEs, a business needs the best mission as steps so that the business that is run can develop and compete with other competitors, there is also a need for an organizational forum to shelter MSME actors so that all MSMEs can become a unified and helping each other among MSME actors, such as information related to exhibitions, the convenience of raw materials and other important information to run a business. Organizational behavior or behavior of MSMEs is also very necessary in achieving improved performance of MSMEs, such as communication, good cooperation and mutual support between MSME actors to run and develop their business.